The Ability of Crystalline and Amorphous Silica from Rice Husk Ash to Perform Quality Hardness for Ceramic Water Filtration Membrane - Zainal, Nur Saadah; Mohamad, Zaleha; Mustapa, Mohammad Sukri; Badarulzaman, Nur Azam; Zulkifli, Abdullah Zulfairis (International Journal of Integrated Engineering, 2019)
Silica is an inexhaustible resource on earth. It can be found in food-based natural resources. The natural tendency of silica mainly is to contribute to the strength and the hardness of the ceramic material. This paper investigates the hardness formed in ceramic filtration membrane made by amorphous and crystalline silica from rice husk. Four samples from this material were studied based on unwashed and washed material with chemical, namely, crystalline silica treated with chemical (CS1), crystalline silica untreated with chemical (CS2), amorphous silica treated with chemical (AS1) and amorphous silica untreated with chemical (AS2). To acquire the silica phases, the rice husk was experienced to combustion process at 700ÂºC and 1000ÂºC for 2 hours. The properties of the silica were obtained by using Scanning electron microscopy (SEM) and x-ray diffractometer (XRD) while the value of the hardness was tested by using microhardness tester machine. As a result from SEM both samples of AS1 and AS2 produced an irregular, crinkled, or grainy surface of silica and for sample CS1 and CS2 produced were flushed, unwrinkled and planar surface. For the high hardness value, crystalline silica treated with chemical (CS1) sample was obtained with 171.0.